Capabilities and Gaps Assessments of Urban Air Quality Manage-ment in Uganda - Amin Tamale Kiggundu (Indonesian Journal of Geography, 2015)
Today, large cities across the globe are facing a pervasive problem of air pollution.  The purpose of this study is to assess the capabilities and gaps in urban air quality management in Uganda as well as proposing strategies for curbing air pollution. This study applied face to face interviews, targeting key informants such as the environmental experts, urbanization researchers and officials from the National Environment Management Authority (NEMA). Results show that rapid motorization, continued dependence on fossil fuels, open waste burning, biomass burning, industrialization, bushfires and urbanization are the key causes of air pollution in Uganda. To reduce air pollution and improve urban air quality it is critical to promote non-motorised mass transport, increase electricity access, regulate open waste burning, establish laboratories, strengthen local research and training capacity, promote collaborations, introduce more fuel efficient vehicles and periodic vehicle inspection and carry out public awareness campaigns about air pollution.